ENTRY, EXIT, DAN TINGKAT KONSENTRASI PADA INDUSTRI MANUFAKTUR DI INDONESIA, 1995-1997 - Satriawan, Elan; Wigati, Hening (Journal of Indonesian Economy and Business, 2002)
Conventional wisdom assumes that concentration rate will change due to the change in entry and exit rate. Entry will negatively influence concentration rate, while exit will change concentration rate positively. This has mainly inspired many governments to adopt what is called the pro-competition policy like deregulation to increase entry rate, hence increasing the competition. Empirically, the relation however, between entry and exit with concentration rate is not such so certain as decribed in theory. The number of entrants (number of firms in broad), as shown in this study, was not the important factor in changing the concentration. It is found that the entrantâs market share and relative size were the significant factors in changing the concentration rate. In addition, product differentiation was the only factors affecting the entry, while product differentitation and capital requirement explained the change in exit.Key words: Entry, Exit, Industrial Concentration, Indonesian Manufacturing.